Autism spectrum disorder in the criminal justice system: a guide to understanding suspects, defendants and offenders with autism - Allely, Clare S. (Routledge, 2022)
What is autism spectrum disorder (ASD)? -- ASD and offending behaviour : why it is important to recognise how ASD symptomology can provide the context of vulnerability for engaging in offending and important considerations when interviewed by police and other criminal justice professionals -- Risk assessment : ASD and issues with current standardised risk assessment -- Prevalence of ASD in forensic settings -- Psychiatric co-morbidity in ASD -- ASD in the courtroom : why it is important to recognise this disorder in defendants -- ASD and arson -- ASD and sexual offences (offline and online) -- ASD and cybercrime -- ASD and violent offending -- ASD and radicalisation and extremism -- ASD and extreme violence -- ASD and stalking -- ASD in the prison environment -- Conclusions and recommendations.